Evaluasi Kinerja Dosen dan Tenaga Kependidikan Selama Work From Home (Wfh): Studi Kasus Di Universitas Negeri Surabaya - Suprapto Suprapto; Suparji Suparji; Sugeng Harianto; Aisyah Endah Palupi; Suwarno Imam Samsul (JPSI (Journal of Public Sector Innovations), 2021)
ABSTRACTThis study aimed to describe the performance of lecturers and administration staff at Universitas Negeri Surabaya (Unesa) during the Covid-19 Pandemic. This study was conducted in Unesa during the Covid-19 pandemic, from March to October 2020. This study was designed as a population study, namely research using all populations as samples that included all Unesa lecturers and administration staffs. The data were collected using open and closed questionnaires with the respondents from lecturers, Head of Subdivisions, and students. The obtained data were analyzed using quantitative descriptive analysis with narrative explanation. The data portrayed the following conclusions: (1) In coping with the Unesa administration staffs performance based on the Heads evaluation, the Head of Subdivision gave excellent appreciation with a mean score of 3.31; (2) In accordance with the Unesa administration staffs performance based on student assessment, the students gave a very good score with a mean score of 3.21; (3) Student assessment of lecturers performance for each faculty and postgraduate program, the highest planning score was postgraduate with an average score of 3.62 and the lowest score was the Faculty of Sports Science with an average score of 3.27, the highest implementation score was postgraduate with a mean score of 3.61 and the lowest was The Faculty of Sports Science with an average score of 3.2, the highest evaluation score was postgraduate with a score of 3.60 and the lowest was the Faculty of Sports Science with a score of 3.26; (4) based on the self-assessment of lecturer performance, the three biggest problems and constraints were 35.15% of signal problems; 20.78% of problems with costs and limited internet quota; and 12.84% of literacy problems. Three suggestions for improvements for online lectures were 33.87% of requirment to improve Vinesa: 32.80% of assistance with facilities and 8.28% of training/preparation/online lecture manuals. ABSTRAKPenelitian ini bertujuan mendeskripsikan kinerja dosen dan tenaga kependidikan Universitas Negeri Surabaya (Unesa) selama masa Pandemi Covid-19. Penelitian ini dilakukan di Unesa selama pandemi Covid-19 yaitu bulan Maret sampai dengan bulan Oktober 2020. Penelitian ini didesain sebagai penelitian populasi yaitu penelitian dengan menggunakan semua populasi sebagai sampel yaitu semua dosen dan tenaga kependidikan Unesa. Data diambil menggunakan teknik pengambilan data berupa angket terbuka dan tertutup dengan responden dosen, Kepala Sub Bagian dan mahasiswa. Data akan dianalisis dengan analisis deskriptif kuantitatif dengan penjelasan secara narasi. Data hasil penelitian memperoleh simpulan sebagai berikut: (1) Kinerja Tendik seluruh Unesa Berdasarkan Penilaian Atasan, Kasubbag memberikan apresiasi yang sangat baik dengan skor rerata 3,31; (2) Rerata Kinerja Tendik seluruh Unesa berdasarkan Penilaian Mahasiswa memberikan penilaian sangat baik dengan skor rerata 3,21; (3) Penilaian Mahasiswa terhadap Kinerja Perkuliahan Dosen Setiap Fakultas dan Pascasarjana, tahap perencanaan skor tertinggi adalah Pascasarjana dengan skor rerata 3,62 dan terendah Fakultas Ilmu Olahraga dengan skor rerata 3,27, tahap pelaksanaan tertinggi Pascasarjana dengan skor rerata 3,61 dan terendah Fakultas Ilmu Olahraga dengan skor rerata 3,2, tahap evaluasi tertinggi Pascasarjana dengan skor 3,60 dan terendah Fakultas Ilmu Olahraga dengan skor 3,26; (4) Berdasarkan Self Assesment Kinerja Dosen, tiga permasalahan dan kendala terbesar adalah 35,15% masalah signal; 20,78% masalah biaya dan keterbatasan kuota internet; dan 12,84% masalah literasi. Tiga saran perbaikan untuk perkuliahan on line adalah 33,87% perlu dilakukannya penyempurnaan Vinesa; 32,80% bantuan fasilitas dan 8,28% adanya pelatihan/persiapan/buku pedoman kuliah daring.